Impact of endoplasmic reticulum aminopeptidases 1 (ERAP1) and 2 (ERAP2) on neutrophil cellular functions - Saulle, Irma; Limanaqi, Fiona; Garziano, Micaela; Murno, Maria Luisa; Artusa, Valentina; Strizzi, Sergio; Giovarelli, Matteo; Schulte, Carsten; Aiello, Jacopo; Clerici, Mario; Vanetti, Claudia; Biasin, Mara (Frontiers in Cell and Developmental Biology, 2025)
IntroductionEndoplasmic reticulum aminopeptidases 1 (ERAP1) and 2 (ERAP2) modulate a plethora of physiological processes for the maintenance of homeostasis in different cellular subsets at both intra and extracellular level.Materials and methodsIn this frame, the extracellular supplementation of recombinant human (rh) ERAP1 and ERAP2 (300 ng/ml) was used to mimic the effect of stressor-induced secretion of ERAPs on neutrophils isolated from 5 healthy subjects. In these cells following 3 h or 24 h rhERAP stimulation by Western Blot, RT-qPCR, Elisa, Confocal microscopy, transwell migration assay, Oxygraphy and Flow Cytometry we assessed: i) rhERAP internalization; ii) activation; iii) migration; iv) oxygen consumption rate; v) reactive oxygen species (ROS) accumulation; granule release; vi) phagocytosis; and vii) autophagy.ResultsWe observed that following stimulation rhERAPs: i) were internalized by neutrophils; ii) triggered their activation as witnessed by increased percentage of MAC-1+CD66b+ expressing neutrophils, cytokine expression/release (IL-1β, IL-8, CCL2, TNFα, IFNγ, MIP-1β) and granule enzyme secretion (myeloperoxidase, Elastase); iii) increased neutrophil migration capacity; iv) increased autophagy and phagocytosis activity; v) reduced ROS accumulation and did not influence oxygen consumption rate.ConclusionOur study provides novel insights into the biological role of ERAPs, and indicates that extracellular ERAPs, contribute to shaping neutrophil homeostasis by promoting survival and tolerance in response to stress-related inflammation. This information could contribute to a better understanding of the biological bases governing immune responses, and to designing ERAP-based therapeutic protocols to control neutrophil-associated human diseases.